2007
DOI: 10.1016/j.jaap.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

On-probe pyrolysis desorption electrospray ionization (DESI) mass spectrometry for the analysis of non-volatile pyrolysis products

Abstract: An on-probe pyrolyzer has been constructed and interfaced with Desorption Electrospray Ionization (DESI) Mass Spectrometry (MS) for the rapid analysis of non-volatile pyrolysis products. The detection and analysis of non-volatile pyrolysis products of peptides, proteins and the synthetic polymer poly(ethylene glycol) are demonstrated with this instrument. The on-probe pyrolyzer can be operated off-line or on-line with the DESI source and was interfaced with a tandem MS (MS/MS) instrument, which allowed for str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In a more recent study implementing LC-MS/MS, Meetani et al also reported that thermal decomposition products of the leu-enkephalin peptide resulted from a sequence ladder fragmentation through the formation of head-to-tail cyclic peptide fragments (and consequently with a −18 amu shift) 24 . Using a combination of MS and tandem MS (MS/MS) for the analysis of non-volatile thermal decomposition products of peptides and proteins, our laboratory discovered that a site-specific fragmentation occurred at the C-terminus of aspartic acid (D) when peptides or proteins were subjected to temperatures between 200–250 °C for 10 seconds 2, 25 . The products of the thermal cleavage at D were easily identified by mass alone since these products resulted from a hydrolysis of the peptide bond C-terminus of D. Other products also detected corresponded to water and ammonia losses.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study implementing LC-MS/MS, Meetani et al also reported that thermal decomposition products of the leu-enkephalin peptide resulted from a sequence ladder fragmentation through the formation of head-to-tail cyclic peptide fragments (and consequently with a −18 amu shift) 24 . Using a combination of MS and tandem MS (MS/MS) for the analysis of non-volatile thermal decomposition products of peptides and proteins, our laboratory discovered that a site-specific fragmentation occurred at the C-terminus of aspartic acid (D) when peptides or proteins were subjected to temperatures between 200–250 °C for 10 seconds 2, 25 . The products of the thermal cleavage at D were easily identified by mass alone since these products resulted from a hydrolysis of the peptide bond C-terminus of D. Other products also detected corresponded to water and ammonia losses.…”
Section: Introductionmentioning
confidence: 99%
“…DESI is an important ionization method in the MS field, and it has been introduced to provide direct ionization of analytes with little or no sample preparation. Besides analyzing solid samples from surfaces [21,[23][24][25][26][27][28][29][30][31], DESI has been extended to directly ionize liquid samples, ranging from small organics to high-mass proteins, in our and other laboratories [9-11, 13, 14, 32-45]. In this study, using DESI-MS to monitor HCHO generated from methanol electro-oxidation has several advantages: (1) compared with DEMS, the detection is convenient and performed at ambient conditions rather than in vacuum; (2) there is no requirement to separate the small potential applied to the electrochemical cell from the high voltage used for DESI spray, which is in contrast to the traditional EC/MS configuration using an ESI interface.…”
Section: Introductionmentioning
confidence: 99%
“…Combined, our previous work conclusively determined that protein sequence is conserved even after being subjected to the harsh conditions required for pyrolysis and that protein identification is possible using pyrolysis as the digestion step in a bottom-up proteomic workflow. The pyrolysis of proteins and peptides has been carried out also in simple furnace-type pyrolyzers and on membrane heaters interfaced with DESI-MS and MALDI-MS detection [7,8]. Also, atmospheric pressure thermal dissociation has been reported on peptide and protein ions in the gas phase, showing a more extensive fragmentation pattern (i.e., b n , y n , and a n -ions) [9] than the fragmentations observed in condensed phase pyrolysis of peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%